Causes of death in patients with atrial fibrillation and a recent acute coronary syndrome or percutaneous coronary intervention: insights from the AUGUSTUS trial. (3rd October 2022) - Guimaraes, P; Wojdyla, D M; Alexander, J H; Goodman, S G; Aronson, R; Windecker, S; Mehran, R; Granger, C B; Lopes, R D
Abstract: Background: Patients with atrial fibrillation (AF) and concomitant coronary artery disease are at increased risk for poor outcomes. Less is known about specific causes of death in this population. Methods: We describe specific causes of death among patients with AF and acute coronary syndrome and/or percutaneous coronary intervention included in the AUGUSTUS trial and followed for 6 months. An independent clinical events committee, blinded to treatment assignment, adjudicated cause of death according to pre-defined criteria. The association between baseline factors and all-cause death was evaluated using Cox proportional hazards modeling. Results: A total of 151 deaths occurred in 4614 patients and were adjudicated as follows: 111 (73.5%) deaths due to cardiovascular (CV) causes and 40 (26.5%) due to non-CV causes. The most common cause of CV death was sudden death (n=39 [35.1%]), followed by myocardial infarction (n=29 [26.1%]) and heart failure (n=24 [21.6%]). The most common causes of non-CV death were infection (n=11 [27.5%]), bleeding (n=8 [20.0%]), and malignancy (n=5 [12.5%]). Increasing age, African American race, history of heart failure, treatment with diuretics, and lower body weight were associated with an increased risk of all-cause death (Table). Conclusions: Among patients with AF and coronary artery disease, cardiovascular causes were responsible for the majority of deaths within 6 months. Our findings provide relevant information to inform the design of future studies in this population. Funding Acknowledgement: Type of funding sources: Private company. Main funding source(s): AUGUTUS was funded by Bristol Myers Squibb and Pfizer.